Acceptance of human excreta derived fertilizers in Swedish grocery stores. (January 2023) - McConville, Jennifer R.; Metson, Geneviève S.; Persson, Hugo
Highlights: Survey of 127 of food retailers attitudes and sustainability policies. Majority feel that excreta derived fertilizers are safe. Struvite and phosphorus from ash were perceived more positively than dry urine. Food retailers worry about possible risks from pharmaceuticals & quality assurance. They are unlikely to push for nutrient reuse unless consumers demand it. Abstract: Safe recycling of nutrients found in human excreta back to agriculture is an important component of a circular economy that can protect waterways and stabilize food prices. Although many technological advances for the recovery of these nutrients exist, large-scale implementation is lacking. A commonly cited barrier is a lack of acceptance of fertilizers from human excreta and for food products grown with such fertilizers. The food retail sector, as an intermediary between producers and consumers, is an important actor with power to influence opinions and purchasing practices. In this study, we surveyed 127 food retailers (stores) and reviewed publicly available retailer sustainability policies to assess acceptance of the use of recycled fertilizers. We gauged acceptance of three products relevant for the Swedish market – struvite, phosphorus from ash, and dehydrated urine. Most respondents felt that all three recovery techniques were unlikely to be harmful either to themselves or to the environment. It was more acceptable to use products further away from human consumption. In general, struvite and phosphorus from ash were perceived more positively. Acceptance of wastewater-derived fertilizers was largely dependent on perceived risks, especially the fate of pharmaceutical residues. While retailers in Sweden are not negative to reuse, they seem unlikely to provide strong support for nutrient recirculation from human excreta unless it becomes a greater concern for the public.